Students’ perspectives on religious moderation: A qualitative study into religious literacy processes - Yusuf Hanafi; Muhammad Saefi; Tsania N. Diyana; M. Alifudin Ikhsan; Nur Faizin; Titis Thoriquttyas; Nurul Murtadho (HTS Teologiese Studies/Theological Studies, 2022)
Research exploring how students develop their perspectives on religious moderation through reading and understanding the Qur’an is underexplored. This study aims to investigate students’ religious literacy tenet as a process of constructing meaning about religious moderation from the verses of the Qur’an. The participants involved were three students with an excellent ability to read the Qur’an and who had a great interest in the study of the Qur’an. The data were collected through the process of reading the verses of the Qur’an and its textual and contextual translation. The results of this study indicate that students with high translation amendments (adding, removing and replacing words and phrases) tend to have more ability to interpret the verses of the Qur’an widely as a form of verbalisation of thoughts.